Recent Developments in Urban Wastewater Management—Insights, Recommendations, and Future Perspectives - Jain, Anshul; Varma, Dr. Hridayesh; Kushwaha, Madhu (Urban Planning and Construction, 2026)
Rapid population growth and intensified human activities such as mining operations, industrial discharge, ore smelting, fossil fuel combustion—particularly coal—along with the agricultural use of arsenic-contaminated water, pesticides, herbicides, and fertilizers have significantly compromised freshwater resources intended for human use. Urban wastewater is characterized by the presence of numerous contaminants that pose toxicity risks to bot microorganisms and higher life forms, thereby necessitating effective treatment strategies. Among emerging solutions, microalgae have received considerable scientific attention due to their strong potential to remove pollutants from both industrial and domestic wastewater streams. Researchers emphasize microalgal-based remediation approaches because of the organisms’ capacity to adapt, grow, and remain metabolically active under diverse and harsh environmental conditions. In addition to pollutant removal, microalgae contribute to carbon dioxide sequestration, offering an added environmental benefit. Their integration into wastewater treatment systems aligns closely with circular bioeconomy principles, as microalgal processes enable the simultaneous generation of valuable bio-based products during conventional treatment operations. This systematic review examines the role of microalgae in urban wastewater treatment, focusing on remediation mechanisms, pollutant removal strategies, and operational approaches. Furthermore, the study explores future opportunities for incorporating microalgal technologies into circular bioeconomy frameworks alongside sustainable wastewater management.